Dynamic reconfiguration of active distribution network considering multiple active management strategies. Issue 3 (February 2019) - Bao, Wei; Zhang, Shaohui; Song, Yichen; Wang, Mingqiang; Li, Xiao; Yan, Yuehao; Fu, Xiaoyong
Abstract: To make full use of various active management resources in ADN to improve the economic efficiency, a dynamic reconfiguration model of active distribution network considering multiple active management (AM) strategies is proposed in this paper. The AM strategies including the configuration of energy storage system, output power controlling of distributed generation, reactive power compensation with static var compensators and packet capacitor switching, tap adjusting with on-load tap changer, and demand side response management. The model tries to minimize the total costs with respect to various operating constraints. Several linearization techniques are applied to formulate the dynamic reconfiguration problem into a mixed-integer linear programming (MILP) model, which guarantees global optimal solution and also reduces the computational difficulty significantly. Finally, the validity and effectiveness of the proposed dynamic reconfiguration model is verified on the IEEE 33-node distribution network system.